Emmer wheat productivity formation depending on pre-sowing seed treatment method in organic and traditional technology cultivation - I. V. Korotkova; T. O. Chaika; T. P. Romashko; O. O. Chetveryk; A. M. Rybalchenko; O. V. Barabolia (Regulatory Mechanisms in Biosystems, 2023)
Determination of chlorophyll and carotenoid content is an important way of obtaining information about the plant's photosynthetic activity as well as an indirect method of assessing the productivity of plant crops, particularly grain crops. The objective of this study was to evaluate the role of chlorophyll and carotenoid in the productivity formation of emmer wheat (Triticum dicoccum (Schrank.) Schuebl) grown under the traditional and organic farming systems and the different pre-sowing seed treatment methods. The base indicators of the photosynthetic apparatus (chlorophyll and carotenoid content, ratio of photosynthetic pigments) were evaluated in the emmer wheat plants as a function of the cultivation technology and pre-sowing seed treatment. The cultivation of the emmer wheat under organic technology was carried out in crop rotation: winter rye – mustard – T. dicoccum wheat. The pre-sowing seed treatment in the traditional technology of emmer wheat cultivation was carried out only by the UV-C irradiation. In the organic technology, both UV-C irradiation and treatment with humic preparation of natural origin “1r Seed Treatment” were used. The content of chlorophyll a (by 9.2%) and chlorophyll b (by 14.5%) increased in the emmer wheat plants under the organic technology cultivation compared to the traditional technology, but with the same method of seed treatment (UV-C irradiation). As a result, the yield increase was 21.0%. The application of the “1r Seed Treatment” humic preparation in the pre-sowing seed treatment led to the increase in yield by ~ 8.0% compared to the plots with UV-C irradiation seeds treatment under organic farming cultivation. An inverse correlation between the ratio of chlorophyll a/ chlorophyll b and the crop yield has been established. The evaluation of economic indicators of the emmer wheat cultivation in the rotation: winter rye-mustard-emmer wheat under organic farming technology, proved its high profitability. So, the photosynthetic pigments’ content and their ratio can be used as the indicators of the efficiency of the introduced elements of agrotechnologies and for predicting future yields.